Islamic Cultural Identity in a Global World Order. - Osman, Noor Mohammad ([s.n], 2012)
Cultural identity is one of the most crucial issues of human existence on the earth. From the beginning of human existence on earth, each person was endowed with certain cultural traits. The identity of an individual is strongly attached to his cultural attributes. A person who believes in Islam and claims to be a Muslim has a greater impact of this belief on his culture and identity. Islam, as a divine religion, concerns one's personal and social life so profoundly that even a converted Muslim in an entirely non-Islamic community would be traced by his Islamic dispositions, norms and practices. The impact of Islamic culture on the identity formation process has greater significance in this modern age, especially because of increasing cultural threats faced by the Muslims worldwide. This study focuses on providing an analysis of Islamic cultural identity in the era of globalization. It attempts to explain the concept of Islamic culture, its historical development and role of Islamic culture in the identity formation process. An analysis of the link between culture and identity will justify its significance for the Muslim communities struggling to sustain cultural heritage in order to save their own identities.